2017
DOI: 10.17576/jsm-2017-4610-25
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Studies of Selected Medicinal Drugs as Dengue Virus-2 Protease Inhibitors

Abstract: Dengue is a potentially deadly disease with no effective drug. An in silico molecular docking was performed using Autodock 4.2.6 to investigate the molecular interactions between protease inhibitors, comprising antibiotic derivatives namely doxycycline (3), rolitetracycline (5) and a non-steroidal anti-inflammatory drug (NSAID), meclofenamic acid (4), against the NS2B-NS3 protease from dengue virus-2 (DENV-2). The non-competitive inhibitor (3) showed lower binding energy (-5.15 kcal/mol) than the predicted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Ariza et al [16] showed that molecular dockings between curcumin and RdRp domain of the NS5 protein, also a key element in the viral replication, with a binding energy of-6.2 Kcal/mol. Rufaidah Othman et al [17] demonstrated the binding interactions of antibiotics pinostrobin (with binding energy of-5.33 Kcal/mol), doxycycline (with binding energy of-5.15 Kcal/mol), 4-hydroxypanduratin A (with binding energy of-4.45 Kcal/mol), meclofenamic acid (with binding energy of-3.64 Kcal/mol) androlitetracycline (with binding energy of-3.21 Kcal/mol) against NS2B-NS3 proteases of dengue viruses. Nasution Aini and Tambunan [18] listed out 18 promising leads to chemotherapy treatments of the dengue diseases based on the comprehensive analyses of molecular docking complexes of 308 diverse molecules bound with NS2B-NS3 proteases of the dengue viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Ariza et al [16] showed that molecular dockings between curcumin and RdRp domain of the NS5 protein, also a key element in the viral replication, with a binding energy of-6.2 Kcal/mol. Rufaidah Othman et al [17] demonstrated the binding interactions of antibiotics pinostrobin (with binding energy of-5.33 Kcal/mol), doxycycline (with binding energy of-5.15 Kcal/mol), 4-hydroxypanduratin A (with binding energy of-4.45 Kcal/mol), meclofenamic acid (with binding energy of-3.64 Kcal/mol) androlitetracycline (with binding energy of-3.21 Kcal/mol) against NS2B-NS3 proteases of dengue viruses. Nasution Aini and Tambunan [18] listed out 18 promising leads to chemotherapy treatments of the dengue diseases based on the comprehensive analyses of molecular docking complexes of 308 diverse molecules bound with NS2B-NS3 proteases of the dengue viruses.…”
Section: Resultsmentioning
confidence: 99%
“…The grid box parameters employed for all target proteins were listed in Table 2 which were inspired by Rabiu et al [20] and Mechqoq et al [21] with some modifications. The Lamarckian genetic algorithm was employed and the parameters were defined according to the Othman et al [22]. The docking process was conducted by utilizing Autodock 4.2.6.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…In the docking exercise, all drugs and the two newly developed compounds were found to bind to the binding pocket at the right side of the active site region (S1 pocket), as observed in Figure 6. Interestingly, this site is much broader and more shallow than the binding pocket at the left region (S2 pocket), 20 yet, most of the interactions were observed to be at this site. It was identified that the S1 region has much more hydrophobic residues compared to the S2 region.…”
Section: Molecular Docking Of the Selected Drugs And Newly Derived Co...mentioning
confidence: 99%